Tracheostomy in head-neck malignancy (Bangladesh Journal of Otorhinolaryngology, 2011)
Objectives: To find out the frequency ,indications and effects of tracheostomy in head-neck malignancy.Methods: Total 100 cases of head-neck malignancy that needed tracheostomy were studied in the department of Otolaryngology and Head-Neck surgery of Dhaka Medical College Hospital and Begum Khaleda Zia Medical College and Shahid Sohrawardi Hospital, Dhaka.Results: The mean age of the subjects was 53.60 years. Out of 100 cases male were 86 and female were 14 with male to female ratio 6.14:1. The highest number of the subjects were related to cultivation and majority of the subjects came from poor socio-economic status. Malignancy in head-neck region is multifactorial disease. Regarding habits 71% were smoker, 21% were habituated with chewing betel nut and leaf. Only 2% were alcoholic. In 93% tracheostomy was done on an emergency basis and rest 7% was elective. Carcinoma of larynx was the most frequent indication (65%), which was followed by carcinoma pyriform fossa (28%), carcinoma base of the tongue (3%), carcinoma tonsil 2% and carcinoma thyroid gland 2%. The rate of complications was 41%. Surgical emphysema was the commonest complications (19%), which were followed by haemorrhage (7%), wound infection (4%), tube displacement (3%), tube blockage (3%), crusting (2%), stomal stenosis and subglottic stenosis (1%). No fatality was found in this study.Conclusion: The rate of complication of tracheostomy is high in patients of head-neck malignancy with respiratory distress. Key words: Tracheostomy; Head Neck Cancer. DOI: 10.3329/bjo.v16i2.6847Bangladesh J Otorhinolaryngol 2010; 16(2): 120-125